Experimental and Analytical Study of Acid Number Variation in Engine Oils Under Operational Contamination - Dykha, M.O.; Hetman, M.V.; Dytyniuk, V.O.; Makovkin, O.M. (Problems of Tribology, 2026)
This paper presents an experimental and analytical study of the variation of the total acid number (TAN) in engine oils under operational contamination. The research is aimed at assessing the correlation between the acidity growth of lubricants and their wear behavior in the four-ball test configuration. Theoretical modeling and experimental testing were performed to identify the parameters of a wear law that incorporates contact pressure, oil viscosity, hardness, and TAN as key variables. The obtained results confirm that the acid number increases significantly during oil operation: from 0.9 to 2.9 mg KOH/g—which leads to an intensified wear rate of the contact surfaces. The proposed model quantitatively describes the relationship between the acidity level and wear intensity and enables prediction of oil performance based on its physicochemical degradation. The developed approach allows for improved evaluation of the residual life of lubricants and optimization of maintenance intervals for internal combustion engines.